Native Top-Down Mass Spectrometry for the Structural Characterization of Human Hemoglobin - Zhang, Jiang (Eur J Mass Spectrom (Chichester, Eng), 2015)
Native mass spectrometry (MS) has become an invaluable tool for the characterization of proteins and non-covalent protein complexes under near physiological solution conditions. Here we report the structural characterization of human hemoglobin (Hb), a 64 kDa oxygen-transporting protein complex, by high resolution native top-down mass spectrometry using electrospray ionization (ESI) and a 15-Tesla Fourier transform ion cyclotron resonance (FTICR) mass spectrometer. Native MS preserves the non-covalent interactions between the globin subunits, and electron capture dissociation (ECD) produces fragments directly from the intact Hb complex without dissociating the subunits. Using activated ion ECD, we observe the gradual unfolding process of the Hb complex in the gas phase. Without protein ion activation, the native Hb shows very limited ECD fragmentation from the N-termini, suggesting a tightly packed structure of the native complex and therefore low fragmentation efficiency. Precursor ion activation allows steady increase of N-terminal fragment ions, while the C-terminal fragments remain limited (38 c ions and 4 z ions on the α chain; 36 c ions and 2 z ions on the β chain). This ECD fragmentation pattern suggests that upon activation, the Hb complex starts to unfold from the N-termini of both subunits, whereas the C-terminal regions and therefore the potential regions involved in the subunit binding interactions remain intact. ECD-MS of the Hb dimer show similar fragmentation patterns as the Hb tetramer, providing further evidence for the hypothesized unfolding process of the Hb complex in the gas phase. Native top-down ECD-MS allows efficient probing of the Hb complex structure and the subunit binding interactions in the gas phase. It may provide a fast and effective means to probe the structure of novel protein complexes that are intractable to traditional structural characterization tools.